Selected Directed Energy Research and Development for U.S. Air Force Aircraft Applications: A Workshop Summary - National Research Council (The National Academies Press, 2013)
The U. S. Air force currently invests significantly in science and technology for directed-energy weapon (DEW) systems. Key elements of this investment include high-energy lasers and high-power microwaves. Other DEW research and development efforts include: optical beam control for high-energy lasers; vulnerability and lethality assessments; and advanced non-conventional and innovative weapons. Selected Directed Energy Research and Development for U.S. Air Force Aircraft Applications is the summary of three workshop sessions convened between February and April, 2013 by the Air Force Studies Board of the National Academies' National Research Council. Representatives from the Air Force science and technology community and DEW experts from the U.S. Army, U.S. Navy, Office of the Secretary of Defense, and the Defense Advanced Research Projects Agency presented and discussed threats that DEW capabilities might defend against and assessments of foreign progress in DEW. This report examines the current status of DEW capabilities both in the U.S. and abroad, and considers future applications of DEW systems.
Keywords: Conflict and Security Issues

Digital Strategy for the Department of the Air Force: Proceedings of a Workshop Series - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The Air Force Studies Board of the National Academies of Sciences, Engineering, and Medicine hosted a three-part workshop series to examine the risks associated with the technical, programmatic, organizational, and governance challenges facing the Department of the Air Force (DAF) in its pursuit of enterprise-wide digital transformation strategies. Senior representatives from government, military, industry, and academia considered the DAF's strategic-level decision-making process as well as how it could achieve unity of effort across all of its digital agencies. Workshop participants discussed organizational and management gaps and weaknesses, as well as technical shortfalls associated with the DAF's digital transformation strategies - for example, the issue of cybersecurity within the context of the DAF's proposed digital strategies. Organizational and management practices from both the public and private sectors were also discussed in light of their potential for adaptation and adoption within the DAF. Sponsored by the U.S. Department of Defense, the three 2-day workshops of the series were held virtually on September 1-2, 2021, September 8-9, 2021, and September 23-24. Panelists at the first workshop explained and discussed the DAF's digital transformation strategy - in particular, the proposed digital architectures and the systems, programs, organizations, and missions to be supported. The second workshop featured panels of information systems experts and managers from industry and other government agencies who discussed their experiences with digital transformations and shared their views of best practices. The third workshop focused on the potential applicability of these lessons learned to the DAF's digital transformation strategy and architecture. This proceedings is a factual summary of what occurred during the workshop series.
Keywords: Conflict and Security Issues; Computers and Information Technology

Testing, Evaluating, and Assessing Artificial Intelligence–Enabled Systems Under Operational Conditions for the Department of the Air Force: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
On June 28-30, 2022, the National Academies of Sciences, Engineering, and Medicine Air Force Studies Board (AFSB) convened a hybrid workshop in support of its consensus study on testing, evaluating, and assessing artificial intelligence (AI)-enabled systems under operational conditions.The information summarized in this Proceedings of a Workshop-in Brief reflects the opinions of individual workshop participants. It should not be viewed as a consensus of the workshop participants, the AFSB, or the National Academies.
Keywords: Conflict and Security Issues

Adapting to Shorter Time Cycles in the United States Air Force: Proceedings of a Workshop Series - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The Air Force Studies Board of the National Academies of Sciences, Engineering, and Medicine hosted a three-part workshop series to investigate the changing paradigm of time and knowledge in modern-day warfare. Sponsored by the U.S. Department of Defense, three 2-day workshops were held virtually on September 16-17, 2020, September 23-24, 2020, and October 1-2, 2020. The objective of the first workshop was to explore the ways in which the U.S. Air Force (USAF) has adjusted its capabilities in response to past shifts in operational timing. In consideration of these past shifts, the second workshop aimed to consider when there could be an advantage to synchronize or desynchronize rates of change with adversaries. Participants had the opportunity to discuss lessons learned and possible changes for USAF Doctrine and future operations. The goal of the third workshop was to examine the implications to doctrine, concepts of operations, and command and control from the recent acceleration of battlespace operations, arising from wide-scale digitization, large-scale sensing, and faster technologies. In all three workshops, speakers explored the broader issues surrounding changing environments, and participants discussed ways to adapt to fundamental changes in the time constants of conflict. This proceedings is a factual summary of what occurred during the workshop series.
Keywords: Conflict and Security Issues

Advanced Battle Management System: Needs, Progress, Challenges, and Opportunities Facing the Department of the Air Force - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The U.S. Department of Defense is pursuing an improved ability to more closely integrate and operate jointly against agile adversaries through Joint All-Domain Command and Control (JADC2). This framework will seamlessly integrate sensors, networks, platforms, commanders, operators, and weapon systems for rapid information collection, decision-making, and projection of joint and multinational forces. The Department of the Air Force's contribution to JADC2 is the Advanced Battle Management System (ABMS). As an evolving system in the early stages of definition, ABMS architecture and its supporting elements remain dynamic. Advanced Battle Management System assesses the technical approach being employed by ABMS and its ability to effectively support the range of system integration desired, while also supporting operational and development agility; and the governance being applied by ABMS and if it is appropriate and sufficient to enable quick development and evolution of capabilities while maintaining appropriate government control over the output.
Keywords: Conflict and Security Issues

Air Force Software Sustainment and Maintenance of Weapons Systems - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Modern software engineering practices, pioneered by the commercial software community, have begun transforming Department of Defense (DoD) software development, integration processes, and deployment cycles. DoD must further adopt and adapt these practices across the full defense software life cycle - and this adoption has implications for software maintenance and software sustainment across the U.S. defense community. Air Force Software Sustainment and Maintenance of Weapons Systems evaluates the current state of software sustainment within the U.S. Air Force and recommends changes to the software sustainment enterprise. This report assesses how software that is embedded within weapon platforms is currently sustained within the U.S. Air Force; identifies the unique requirements of software sustainment; develops and recommends a software sustainment work breakdown structure; and identifies the necessary personnel skill sets and core competencies for software sustainment.
Keywords: Conflict and Security Issues

Software Sustainment and Maintenance of Weapons Systems for the United States Air Force: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
On February 27-March 1, 2019, the National Academies of Sciences, Engineering, and Medicine's Air Force Studies Board convened a workshop in Washington, D.C., on U.S. Air Force (USAF) software sustainment and maintenance of weapons systems. This workshop was conducted as part of a broader study conducted by the Committee on Air Force Software Sustainment and Maintenance of Weapon Systems that is focused on addressing challenges and identifying opportunities to effectively design and execute sustainment planning across USAF systems and platforms. During the workshop, committee members heard from a wide range of subject-matter experts in software sustainment from government to academia to examine how the USAF can improve planning, implementation, and management of software sustainment and maintenance of weapons systems. This publication highlights the discussion and presentations of that event.
Keywords: Conflict and Security Issues

Test and Evaluation Challenges in Artificial Intelligence-Enabled Systems for the Department of the Air Force - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The Department of the Air Force (DAF) is in the early stages of incorporating modern artificial intelligence (AI) technologies into its systems and operations. The integration of AI-enabled capabilities across the DAF will accelerate over the next few years. At the request of DAF Air and Space Forces, this report examines the Air Force Test Center technical capabilities and capacity to conduct rigorous and objective tests, evaluations, and assessments of AI-enabled systems under operational conditions and against realistic threats. This report explores both the opportunities and challenges inherent in integrating AI at speed and at scale across the DAF.
Keywords: Computers and Information Technology; Conflict and Security Issues

Energy Challenges and Opportunities for Future Data-Driven Operations in the United States Air Force: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
On April 27-29, 2020, the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop on U.S. Air Force (USAF) data-driven operations’ energy challenges as part of a broader study focused on this topic. Subject experts from government, industry, and academia discussed steps and plans the USAF is taking and/or should be considering now to successfully develop, deploy, and sustain the weapons systems needed to compete in an emerging information-rich environment. This publication summarizes the presentations and discussions from the workshop.
Keywords: Conflict and Security Issues; Energy and Energy Conservation

Development Planning: A Strategic Approach to Future Air Force Capabilities - National Research Council (The National Academies Press, 2014)
The development and application of technology has been an essential part of U.S. airpower, leading to a century of air supremacy. But that developmental path has rarely been straight, and it has never been smooth. Only the extraordinary efforts of exceptional leadership - in the Air Forces and the wider Department of Defense, in science and in industry - have made the triumphs of military airpower possible. Development Planning provides recommendations to improve development planning for near-term acquisition projects, concepts not quite ready for acquisition, corporate strategic plans, and training of acquisition personnel. This report reviews past uses of development planning by the Air Force, and offers an organizational construct that will help the Air Force across its core functions. Developmental planning, used properly by experienced practitioners, can provide the Air Force leadership with a tool to answer the critical question, Over the next 20 years in 5-year increments, what capability gaps will the Air Force have that must be filled? Development planning will also provide for development of the workforce skills needed to think strategically and to defectively define and close the capability gap. This report describes what development planning could be and should be for the Air Force.
Keywords: Conflict and Security Issues

The Role of Experimentation Campaigns in the Air Force Innovation Life Cycle - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The Air Force (USAF) has continuously sought to improve the speed with which it develops new capabilities to accomplish its various missions in air, space, and cyberspace. Historically, innovation has been a key part of USAF strategy, and operating within an adversary's OODA loop (observe, orient, decide, act) is part of Air Force DNA. This includes the ability to deploy technological innovations faster than do our adversaries. The Air Force faces adversaries with the potential to operate within the USAF's OODA loop, and some of these adversaries are already deploying innovations faster than the USAF. The Role of Experimentation Campaigns in the Air Force Innovation Life Cycle examines the current state of innovation and experimentation in the Air Force and best practices in innovation and experimentation in industry and other government agencies. This report also explores organizational changes needed to eliminate the barriers that deter innovation and experimentation and makes recommendations for the successful implementation of robust innovation and experimentation by the Air Force.
Keywords: Conflict and Security Issues

Owning the Technical Baseline for Acquisition Programs in the U.S. Air Force - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
While there are examples of successful weapon systems acquisition programs within the U.S. Air Force (USAF), many of the programs are still incurring cost growth, schedule delays, and performance problems. The USAF now faces serious challenges in acquiring and maintaining its weapons systems as it strives to maintain its current programs; add new capabilities to counter evolving threats; and reduce its overall program expenditures. Owning the technical baseline is a critical component of the Air Force's ability to regain and maintain acquisition excellence. Owning the technical baseline allows the government acquisition team to manage and respond knowledgeably and effectively to systems development, operations, and execution, thereby avoiding technical and other programmatic barriers to mission success. Additionally, owning the technical baseline ensures that government personnel understand the user requirements, why a particular design and its various features have been selected over competing designs, and what the options are to pursue alternative paths to the final product given unanticipated cost, schedule, and performance challenges. Owning the Technical Baseline for Acquisition Programs in the U.S. Air Force discusses the strategic value to the Air Force of owning the technical baseline and the risk of not owning it and highlights key aspects of how agencies other than the Air Force own the technical baseline for their acquisition programs. This report identifies specific barriers to owning the technical baseline for the Air Force and makes recommendations to help guide the Air Force in overcoming those barriers.
Keywords: Conflict and Security Issues

Evaluation of U.S. Air Force Preacquisition Technology Development - National Research Council (The National Academies Press, 2011)
From the days of biplanes and open cockpits, the air forces of the United States have relied on the mastery of technology. From design to operation, a project can stretch to 20 years and more, with continuous increases in cost. Much of the delay and cost growth afflicting modern United States Air Force (USAF) programs is rooted in the incorporation of advanced technology into major systems acquisition. Leaders in the Air Force responsible for science and technology and acquisition are trying to determine the optimal way to utilize existing policies, processes, and resources to properly document and execute pre-program of record technology development efforts, including opportunities to facilitate the rapid acquisition of revolutionary capabilities and the more deliberate acquisition of evolutionary capabilities. Evaluation of U.S. Air Force Preacquisition Technology Development responds to this need with an examination of the current state of Air Force technology development and the environment in which technology is acquired. The book considers best practices from both government and industry to distill appropriate recommendations that can be implemented within the USAF.
Keywords: Conflict and Security Issues

Early Sustainment Planning for the United States Air Force: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On December 3-5, 2018, the National Academies of Sciences, Engineering, and Medicine convened a workshop in Washington, D.C., on U.S. Air Force (USAF) sustainment planning early in the development life cycle. This workshop was conducted as part of a broader study on addressing challenges and identifying opportunities to effectively design and execute sustainment planning across USAF systems and platforms. This publication summarizes the presentations and discussions from the workshop.
Keywords: Conflict and Security Issues

Zero-Sustainment Aircraft for the U.S. Air Force: A Workshop Summary - National Research Council (The National Academies Press, 2013)
Overall Air Force weapon system sustainment (WSS) costs are growing at more than 4 percent per year, while budgets have remained essentially flat. The cost growth is due partly to aging of the aircraft fleet, and partly to the cost of supporting higher-performance aircraft and new capabilities provided by more complex and sophisticated systems, such as the latest intelligence, surveillance, and reconnaissance (ISR) platforms. Furthermore, the expectation for the foreseeable future is that sustainment budgets are likely to decrease, so that the gap between budgets and sustainment needs will likely continue to grow wider. Most observers accept that the Air Force will have to adopt new approaches to WSS if it is going to address this problem and remain capable of carrying out its missions. In this context, the original intent of this 3-day workshop was to focus on ways that science and technology (S&T) could help the Air Force reduce sustainment costs. However, as the workshop evolved, the discussions focused more and more on Air Force leadership, management authority, and culture as the more critical factors that need to change in order to solve sustainment problems. Many participants felt that while S&T investments could certainly help—particularly if applied in the early stages ("to the left") of the product life cycle—adopting a transformational management approach that defines the user-driven goals of the enterprise, empowers people to achieve them, and holds them accountable, down to the shop level. Several workshop participants urged Air Force leaders to start the process now, even though it will take years to percolate down through the entire organization. These sustainment concerns are not new and have been studied extensively, including recent reports from the National Research Council's Air Force Studies Board and the Air Force Scientific Advisory Board.
Keywords: Conflict and Security Issues; Space and Aeronautics

Creating Capability for Future Air Force Innovation: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The National Academies of Science, Engineering, and Medicine convened a workshop on March 12-14, 2018 at the behest of the U.S. Air Force Vice Chief of Staff. The goal of the workshop was to address the challenge of innovation adoption within the organization with a focus on understanding how complex organizations envision their future state, embrace innovation, and overcome impediments to change. Against this backdrop, workshop participants explored high-impact actions that the Air Force could quickly adopt that would unleash a culture of innovation. This publication briefly summarizes the presentations and discussions from the workshop.
Keywords: Conflict and Security Issues; Behavioral and Social Sciences

The Air Force Health Study Assets Research Program - Institute of Medicine (The National Academies Press, 2015)
The Air Force Health Study (AFHS) is a longitudinal, prospective epidemiologic study of more than 2,700 men followed for approximately 20 years. This cohort participated in up to six intensive physical examinations with high rates of compliance. In addition to a complete record of clinical measurements and observations collected at these exams, serum and other biological samples were obtained and preserved. Extensive questionnaires addressing health, lifestyle, and socioeconomic status were administered during each exam, and other information was obtained about the participants' employment, families and offspring, and potential sources of environmental exposures. While the study was completed in 2006, the extensive health data linked to several types of longitudinally collected biologic specimens - some 91,000 serum, whole blood, urine, semen, and adipose tissue specimens - remain a resource for additional research. The AFHS assets are exceptional in the sheer multitude and range of types of information available for each participant. The longitudinal nature of the AFHS - with its extended follow-up, high rates of retention, and repeat biological samples - provides a valuable opportunity for research beyond the original aims of the study. Currently, the Institute of Medicine is the custodian of these assets. The Air Force Health Study Assets Research Program outlines the feasibility and advisability of maintaining the biospecimens based on interest generated from the general scientific community and results of pilot projects and other research projects using the AFHS assets. According to this report, sustaining access to the AFHS biospecimens and data benefits the veterans community and the public at large, who will gain from the information derived from studies of the assets. . This report discusses the scientific value of the AFHS data and biospecimens and the lessons learned in managing access to the assets.
Keywords: Health and Medicine; Conflict and Security Issues

Examination of the U.S. Air Force's Aircraft Sustainment Needs in the Future and Its Strategy to Meet Those Needs - National Research Council (The National Academies Press, 2011)
The ability of the United States Air Force (USAF) to keep its aircraft operating at an acceptable operational tempo, in wartime and in peacetime, has been important to the Air Force since its inception. This is a much larger issue for the Air Force today, having effectively been at war for 20 years, with its aircraft becoming increasingly more expensive to operate and maintain and with military budgets certain to further decrease. The enormously complex Air Force weapon system sustainment enterprise is currently constrained on many sides by laws, policies, regulations and procedures, relationships, and organizational issues emanating from Congress, the Department of Defense (DoD), and the Air Force itself. Against the back-drop of these stark realities, the Air Force requested the National Research Council (NRC) of the National Academies, under the auspices of the Air Force Studies Board to conduct and in-depth assessment of current and future Air Force weapon system sustainment initiatives and recommended future courses of action for consideration by the Air Force. Examination of the U.S. Air Force's Aircraft Sustainment Needs in the Future and Its Strategy to Meet Those Needs addresses the following topics: Assess current sustainment investments, infrastructure, and processes for adequacy in sustaining aging legacy systems and their support equipment. Determine if any modifications in policy are required and, if so, identify them and make recommendations for changes in Air Force regulations, policies, and strategies to accomplish the sustainment goals of the Air Force. Determine if any modifications in technology efforts are required and, if so, identify them and make recommendations regarding the technology efforts that should be pursued because they could make positive impacts on the sustainment of the current and future systems and equipment of the Air Force. Determine if the Air Logistics Centers have the necessary resources (funding, manpower, skill sets, and technologies) and are equipped and organized to sustain legacy systems and equipment and the Air Force of tomorrow. Identify and make recommendations regarding incorporating sustainability into future aircraft designs.
Keywords: Conflict and Security Issues; Space and Aeronautics

Owning the Technical Baseline for Acquisition Programs in the U.S. Air Force: A Workshop Report - National Research Council (The National Academies Press, 2015)
The U.S. Air Force has experienced many acquisition program failures - cost overruns, schedule delays, system performance problems, and sustainability concerns - over program lifetimes. A key contributing factor is the lack of sufficient technical knowledge within the Air Force concerning the systems being acquired to ensure success. To examine this issue, the Assistant Secretary of the Air Force for Acquisition requested that the Air Force Studies Board of the National Research Council undertake a workshop to identify the essential elements of the technical baseline - data and information to establish, trade-off, verify, change, accept, and sustain functional capabilities, design characteristics, affordability, schedule, and quantified performance parameters at the chosen level of the system hierarchy - that would benefit from realignment under Air Force or government ownership, and the value to the Air Force of regaining ownership under its design capture process of the future. Over the course of three workshops from November 2014 through January 2015, presenters and participants identified the barriers that must be addressed for the Air Force to regain technical baseline control to include workforce, policy and process, funding, culture, contracts, and other factors and provided a terms of reference for a possible follow-on study to explore the issues and make recommendations required to implement and institutionalize the technical baseline concept. Owning the Technical Baseline for Acquisition Programs in the U.S. Air Force summarizes the presentations and discussion of the three workshops.
Keywords: Conflict and Security Issues

Future Air Force Needs for Survivability - National Research Council (The National Academies Press, 2006)
A key technical issue for future Air Force systems is to improve their ability to survive. Increased use of stealth technology is proposed by many to be the major element in efforts to enhance survivability for future systems. Others, however, suggest that the high cost and maintenance required of stealth technology make increased speed potentially more productive. To help address this issue, the Air Force asked the NRC to investigate combinations of speed and stealth that would provide U.S. aircraft with a high survival capability in the 2018 period, and to identify changes in R&D plans to enable such aircraft. This report presents a review of stealth technology development; a discussion of possible future missions and threats; an analysis of the technical feasibility for achieving various levels of stealth and different speeds by 2018 and of relevant near-term R&D needs and priorities; and observations about the utility of speed and stealth trade-offs against evolving threats.
Keywords: Conflict and Security Issues; Space and Aeronautics